EFL Learner’s Beliefs in Learning Grammar - Susanti, Susanti; Emsil, Sucitra Juliana; Halim, Abdul; Atikah, Dewi (AL LUGHAWIYAAT, 2023)
This qualitative study aims to identify students’ beliefs about learning grammar. Data were collected by using questionnaire and reflection of twenty-five English Education Department students. The data were analyzed based on thematic analysis which consists of six themes emerged. This study focuses on students’ beliefs in learning grammar particularly on the aspect of the importance of grammar, learners’ needs in learning grammar, learners’ strategy in learning grammar, learners’ beliefs about difficulty of grammar, learners belief on the error correction and feedback and learners confidence of using grammar in communication. This will provide information to lecturers and universities to take advantage of beliefs in learning grammar. This study thus implies that the educators can design the lesson by taking into consideration the students’ beliefs.Keywords: Importance of Grammar; Learning Grammar; Students’ Beliefs.